POLITICAL LEADERSHIP: KEY TO SUCCESS FOR THE EXERCISE OF THE PRESIDENCY OF A GOVERNMENT - Sánchez Soto, Rubén Gómez (2022)
Citizens of a country are required to have political participation; since they need to evaluate the functioning of governments, qualify the positive results, and even more so the negative results. As a result of this democratic exercise, it is possible to qualify the policy proposals and plans of the presidential candidates to check if they have really been fulfilled. This is a right, moreover, the results that are achieved in the quality of democracy will depend on the exercise of democracy, civil liberties, the full exercise of pluralism (a system that accepts and tolerates differences of thoughts). But, everything mentioned begins with the electoral process through which citizens need to participate and choose the best option; precisely here is the dilemma, on how to properly exercise this right. In this paper, the factors that citizens need to evaluate of the candidates' proposals will be considered, and also qualify the political leadership of each one, since as has been evidenced the following relationship: “There is a relationship between political leadership and quality of democracy”, for this reason it is essential that citizens have the minimum conditions to make a very serious selection of the best government option for their countries.